Groundwater nitrogen and chloride following closure of an earthen manure storage in southern Alberta. Issue 2 (2nd February 2021) - Kohn, Jacqueline; Iwanyshyn, Mike; Olson, Barry M.
Abstract: Earthen manure storage (EMS) facilities no longer in operation present a risk to the environment, and there is limited guidance to support the planning and implementation of EMS closures. A combined dairy and feedlot in southern Alberta, Canada, had an EMS in operation for about 55 yr. The dairy portion ceased operation in 2015, and the EMS was emptied; however, no specific steps for permanent closure to minimize possible contamination were followed. The objective of this study was to document changes in shallow groundwater quality following an EMS closure. This EMS was already instrumented to assess its effect on the groundwater quality as part of a long‐term study prior to closure. Eight groundwater monitoring wells were installed 2–38 m from the EMS in up‐ and downgradient positions in 2010 and 2011. Groundwater samples were collected about three times annually prior to and for 4 yr after the EMS closure and were analyzed for NO3 –N, NH3 –N, and Cl − . Wells screened at more than 8 m deep were not affected by the EMS prior to or after closure. However, in shallower wells, groundwater NO3 –N concentration increased to a maximum 3 yr after closure (in 2018) and then decreased afterward. In a shallow well 40 m downgradient from the EMS, the NO3 –N concentrations decreased from 31 mg L −1 in 2015 to 5 mg L −1 in 2019, and the Cl − concentration decreased from 64 to 53 mg L −1, suggesting the contamination plume had dispersed. However, the EMS was still a source of contamination because high concentrations of NO3 –N (0.05–40 mg L −1 ) and Cl − (43–862 mg L −1 ) were present in wells adjacent to the EMS 4 yr after closure. Core Ideas: Material left in an earthen manure storage (EMS) contributed N to the groundwater for 4 yr after closure. At 40 m from the EMS, groundwater nitrate‐N was reduced significantly after closure. Soil may need to be removed to eliminate the source of contamination after closure.